PERBAIKAN POSTUR KERJA MELALUI PERANCANGAN ULANG DESAIN TROLI PADA AKTIVITAS MANUAL MATERIAL HANDLING - Simatupang, Ricky Perdana; Sirait, Ganda (LPPM Universitas Putera Batam, 2022)
Manual transfer of materials using unsupportive tools causes difficulties and complaints that result in bodily injuries, such as shifting of the base of the spine, irreversible changes in body shape, and other injuries. Shimano Batam owns a Subcon company called PT. Citra Jaya Hope. Workers in the shop section perform manual material handling tasks. Considering the problem setting, research is needed using Rapid Entire Body Assessment (REBA) and QFD techniques. The results of the trolley design obtained by QFD in this study were validated through recalculation using the REBA method. The total score achieved is 4, indicating a moderate risk level which is almost the same as a low risk level.